Gambaran Kondisi Ibu Hamil Menurut Pemeriksaan Laboratorium - Widya Wati (STIKES Citra Delima Bangka Belitung, 2020)
Antenatal care, which consists of a health check-up process, observation and education for pregnant women, requires laboratory tests to detect abnormalities early during pregnancy. This study aims to obtain a description of the condition of pregnant women at Sungailiat Health Center based on the results of laboratory examinations. The research sample was pregnant women who were examined at the Sungailiat Health Center laboratory from January to July 2020, whose data were collected through the Puskesmas information system (simpus) and analyzed descriptively and graphically. It was found that 26.5% of pregnancies that occurred in women aged under 20 years and over 35 years and 3.5% of pregnant women aged under 20 years and between 20-35 years suffered from anemia. Hepatitis B affects 1.8% of pregnant women due to the hygiene and sanitation conditions of the living environment. There were no problems related to syphilis and HIV, but 2.2% of pregnant women had proteinuria.